Organizational and Economic Platform of Entrepreneurship In Rural Areas (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The gradual change of organizational and legal forms of entrepreneurship, business functions, scopes and fields of application had a significant impact on the terminological essence included in its interpretation.